Pengaruh inflasi dan nilai kurs terhadap return saham pada perusahaan perbankan dalam indeks LQ45 Bursa Efek Indonesia - Sihombing, Indri (Fakultas Ekonomi Prodi Akuntansi, 2025)
This study uses a quantitative deskriptif approach, analyzing 5 of perbankan companies in the LQ45 index as a sample for assessing the impact of inflation and exchange rate on stock return. The analysis's findings indicate that there is no significant impact of the two variables on the return on equity of the LQ45 bank's shares on the Indonesian Stock Exchange for the years 2018–2023. However, the analysis shows that inflation and exchange rate had an impact on the return on equity of the bank's stock in LQ45 during the same time period. Because of this, the study indicates that fluctuations in inflation and exchange rate can affect the return on equity of banks in the Indonesian market.